PDB, Pertumbuhan Dan Pembangunan Ekonomi Di Indonesia - Yanuar (Jurnal Ekonomi, 2010)
The Gross Domestic Product (GDP) of a country is calculated by using the production approach and is influenced by capital, human resources, natural resources, and entrepreneurship. Indonesia with the four most tremendous amounts of resources in the world have actually the potential to be a rich nation that is able to improve its people's welfare. But seen from its GDP aspect, Indonesia is only at number 142 in the world. In order to realize such potential resources, there are some issues that have to be solved. First, almost a half (44.93%) of the participation level of the Indonesian workforce is elementary school graduates. Second, the loan interest rate is considered high from 12% to 15%. Third, there is only 0.18 Yo of the population who are entrepreneurs. And fourth, the corruption problems have not been solved significantly; for example, now Indonesia is still considered the most corrupt country in the Asia Pacific region. Thus, if the Indonesian government wants to improve its citizen welfare, it has to improve the quality of the workforce, motivate more people to be entrepreneurs, reduce the interest rate below 10% and eradicate corruption.